Enhancing the Effectiveness for Agricultural Production Base on Sufficiency Economy Philosophy - สมยานะ วีระศักดิ์ (Community and Social Development Journal, 2019)
This research aims to find ways to enhance the effectiveness of agricultural production of the community in Chiang Mai province population 207subdistrict organizations. The community has the potential on Sufficiency Economy Philosophy (SEP). The qualitative research was to analyze the community context of samples 10 subdistrict organizations using SWOT analysis in order to determine the factors that promote or hinder the potential of the group. The focus group is a qualitative method used to find ways to increase the productivity of farmers. The quantitative analysis of soil nutrient values includes a comparative performance measurement by produetion efficiency before and after the implementation of the SEP to the major crops in Chiang Mai, namely, longan, passion fruit, onion, and riceberry. The research found that the potential agricultural production groups in Chiang Mai could apply SEP in three guidelines; 1) Soil management, nutrient analysis of soil found that the soil is fertile ground for production. Thus, the soil is slightly improved using organic fertilizer from the agricultural residues in the community to reduce agricultural expenditure. 2) Increase productivity, all farmer groups have the production techniques in crop types, soil management, pest management, and development to full-scale organic farming. 3) Reduce costs in order to increase production efficiency. The research could enhance the average productivity by 46.95% split according to the type of agricultural products. The most effective production value of passion fruit is 73.39%, followed by the production efficiency values of longan (59.36%), onion (42.32%), and riceberry (12.74%). These study can enhancing the efficiency for agriculture production.